OPTIMASI MALTODEKSTRIN DAN EKSTRAK SECANG PADA SERBUK MINUMAN JAHE MENGGUNAKAN MIXTURE DESIGN : OPTIMASI MALTODEKSTRIN DAN EKSTRAK SECANG PADA SERBUK MINUMAN JAHE MENGGUNAKAN MIXTURE DESIGN - Wiyono, Andi Eko; Prameswari, Dinda Putri; Kuswardhani, Nita (BPFP Faperta UNIB, 2024)
Ginger and secang can be developed into functional food products in the form of spice drink powder. The process of making ginger and secang spice drink powder can be done using the foam drying technique. This research aims to obtain the optimum formula for ginger and secang spice drink powder using the foam mat drying technique, as well as knowing the physical and chemical characteristics of the ginger and secang powder spice drink in the optimum formula. The experimental design used the mixture design method in the application of Simplex Lattice Design with Design Expert version 13 software. The formulation of ingredients was carried out using two factors, namely variations of maltodextrin and secang extract. The research results showed that the optimum ginger and secang spice drink powder formula was formula 5 (10% maltodextrin; 40% secang extract) with a desirability value of 0.722. Results: The optimum physical and chemical characteristics of the formula are water content of 3.76%; hygroscopicity of 13.68%; a* value of 8.24; aroma hedonic quality of 3.93; color hedonic quality of 4.67; °hue value of 46.74°; solubility 88.018%; and antioxidant activity 31.8%.